Non-inflammatory destructive periodontal disease: a clinical, microbiological, immunological and genetic investigation - Carlos Eduardo Repeke; Cristina Ribeiro Cardoso; Marcela Claudino; Elcia Maria Silveira; Ana Paula Favaro Trombone; Ana Paula Campanelli; João Santana Silva; Walter Martins Júnior; Gustavo Pompermaier Garlet (University of São Paulo, 2012)
Periodontitis comprises a group of multifactorial diseases in which periodontopathogens accumulate in dental plaque and trigger host chronic inflammatory and immune responses against periodontal structures, which are determinant to the disease outcome. Although unusual cases of non-inflammatory destructive periodontal disease (NIDPD) are described, their pathogenesis remains unknown. A unique NIDPD case was investigated by clinical, microbiological, immunological and genetic tools. The patient, a non-smoking dental surgeon with excessive oral hygiene practice, presented a generalized bone resorption and tooth mobility, but not gingival inflammation or occlusion problems. No hematological, immunological or endocrine alterations were found. No periodontopathogens (A. actinomycetemcomitans, P. gingivalis, F. nucleatum and T. denticola) or viruses (HCMV, EBV-1 and HSV-1) were detected, along with levels of IL-1β and TNF-a in GCF compatible with healthy tissues. Conversely ALP, ACP and RANKL GCF levels were similar to diseased periodontal sites. Genetic investigation demonstrated that the patient carried some SNPs, as well HLA-DR4 (*0404) and HLA-B27 alleles, considered risk factors for bone loss. Then, a less vigorous and diminished frequency of toothbrushing was recommended to the patient, resulting in the arrest of alveolar bone loss, associated with the return of ALP, ACP and RANKL in GCF to normality levels. In conclusion, the unusual case presented here is compatible with the previous description of NIDPD, and the results that a possible combination of excessive force and frequency of mechanical stimulation with a potentially bone loss prone genotype could result in the alveolar bone loss seen in NIDPD.